2023
DOI: 10.3389/ijph.2023.1605312
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Disability Inequality in Unmet Healthcare Needs and Preventable Hospitalizations: An Analysis of the Korea Health Panel

Abstract: Objectives: This study examines the inequality between people with and without disabilities regarding unmet healthcare needs and preventable hospitalization.Methods: We used the Korea Health Panel of 2016–2018; the final analytical observations were 43,512, including 6.95% of persons with disabilities. We examined the differences in contributors to the two dependent variables and decomposed the observed differences into explained and unexplained components using the Oaxaca-Blinder approach.Results: Unmet healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Another study found that 17.0% of people with disabilities experienced unmet healthcare needs in 2017 compared to 8.8% of people without disabilities in 2016 [ 5 ]. These results confirm that people with disabilities have more difficulties accessing healthcare services [ 28 ]. Moreover, these difficulties increased after the outbreak of COVID-19.…”
Section: Discussionsupporting
confidence: 75%
“…Another study found that 17.0% of people with disabilities experienced unmet healthcare needs in 2017 compared to 8.8% of people without disabilities in 2016 [ 5 ]. These results confirm that people with disabilities have more difficulties accessing healthcare services [ 28 ]. Moreover, these difficulties increased after the outbreak of COVID-19.…”
Section: Discussionsupporting
confidence: 75%
“…A study from Greece showed that unmet needs for dental care were 1.8 times higher in disabled people than those who were not, and approximately 25% of disabled people did not receive dental care for economic reasons [32]. Socioeconomic factors, such as income level, were identi ed as one of the reasons for this gap [33][34][35]. A study from the United Kingdom also showed that disabled people had a higher rate of unmet need for medical care than people who were not disabled, and that women had a higher rate of unmet need for medical care than men within the disabled group [36].…”
Section: Introductionmentioning
confidence: 99%
“…Most policies for reducing the prevalence of UHN are generally centered on vulnerable populations, including the elderly [4,7,9,15,16]. Previous studies on the elderly population were mainly conducted to identify factors affecting UHN [4,5,[17][18][19][20] and grasp the healthcare needs of older people with chronic diseases and disability [15,17,21]. Prior studies were also conducted on the determinants of inequality in UHN [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the elderly population were mainly conducted to identify factors affecting UHN [4,5,[17][18][19][20] and grasp the healthcare needs of older people with chronic diseases and disability [15,17,21]. Prior studies were also conducted on the determinants of inequality in UHN [21][22][23]. According to previous studies, UHN among the elderly is due to various factors, including socio-demographic or economic variables, such as sex, age, education, and income level [11,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation